Climate policy integration: taking advantage of policy windows? An analysis of the energy and environment sectors in Mexico (1997–2018). Issue 1 (2nd January 2022) - García Hernández, Alma Lucía; Lucatello, Simone
ABSTRACT: Given the crosscutting character of climate change, improving our understanding of its integration into sectorial policy domains is relevant. We contribute empirically with a case study in Mexico where we analyze climate policy integration in terms of policy outputs and processes. Firstly, we adapted an approach to measure events of regulatory output change and applied it to our original dataset of changes in Mexican environmental and energy laws and regulations between 1997 and 2018. Secondly, based on expert interviews and using the multiple streams as theoretical framework, we explored the role of policy entrepreneurs on influencing policy change towards climate policy integration, in particular the enactment of the law for energy transition in 2015. The Energy Reform in 2013, which aimed at increasing private participation in fossil fuels production, was framed as a solution to the problem of 'uncertainties over oil reserves and energy demand growth'. Paradoxically, policy entrepreneurs advocated for a transition toward clean electricity as a solution to the same problem. They also identified the 21st UNFCCC Conference of the Parties as an event influencing the political stream and opening a window of opportunity for the enactment of the law for energy transition.